PENGARUH MOTIVASI DAN PRESTASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI NEGERI SIPIL PADA SEKRETARIAT DAERAH KABUPATEN NGANJUK - Muhammad Bawono (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2016)
Implementation of development is a process that requires good planning and implementation, one important aspect is the quality and support of human resources. The success of development depends heavily on humans to do the job, however, that dimliki by a nation, natural resources, social, cultural, and others would be meaningless if it is not handled by qualified human. The problems that are taken in this research is the influence between motivation and work performance to the satisfaction of the Civil Service at the District Secretariat Nganjuk. The purpose of this study is to determine and analyze the influence of motivation on job satisfaction of Civil Servants at the District Secretariat Nganjuk, to determine and analyze the effect of work performance on job satisfaction of Civil Servants at the District Secretariat Nganjuk and to know and analyze the influence of motivation and work performance on job satisfaction Civil Servants at the District Secretariat Nganjuk. The population in this study is a Civil Servant Regional Secretariat Nganjuk with samples of the Civil Service General Administrative Assistant Regional Secretariat Nganjuk. Hypothesis testing is done by distributing questionnaires as much as 30 Civil Servants at the Regional Secretariat Nganjuk. The analysis used is validity, reliability, hypothesis testing, with SPSS version 17 using multiple linear regression analysis. By using multiple regression analysis can be concluded that the regression coefficient (b1) work motivation (X1) of 0.593, the regression coefficient (b2) work performance variables (X2) is 0.424, both values between work motivation and job performance differences where work motivation greater influence on job satisfaction than work performance variables. From the results of regression analysis also found together independent variables have a significant effect on the dependent variable. This is evident from the calculated F value of 160 712 with a significance value (sig) of 0.000 for significance value (sig) is much smaller than 0.05 that motivation and job performance together effect on job satisfaction. So the hypothesis which states that motivation and job performance together positive effect on job satisfaction can be accepted. It can be concluded also that motivation and job performance have a positive influence and significant impact on job satisfaction Civil Servants Regional Secretariat Nganjuk accordance with the results of counting partial test (t test), work motivation with t value of work motivation 7.310 sig 0,000 because of significant value <0.05 then the motivation variable significant effect on job satisfaction, while the value of work performance variables t 4.720 0.000 sig also significant effect on job satisfaction because of its significance in job satisfaction <0.05.